2010
DOI: 10.1074/jbc.m109.058552
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in the Subcellular Distribution of Gpd1p in Response to Cell Stress

Abstract: Gpd1p is a cytosolic NAD؉ -dependent glycerol 3-phosphate dehydrogenase that also localizes to peroxisomes and plays an essential role in the cellular response to osmotic stress and a role in redox balance. Here, we show that Gpd1p is directed to peroxisomes by virtue of an N-terminal type 2 peroxisomal targeting signal (PTS2) in a Pex7p-dependent manner. Significantly, localization of Gpd1p to peroxisomes is dependent on the metabolic status of cells and the phosphorylation of aminoacyl residues adjacent to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 74 publications
3
81
0
Order By: Relevance
“…Interestingly, it is reported that peroxisomal proteins can be differentially localized within the cell depending on differential splicing, multiple targeting signals or phosphorylation (Fordor et al 2012;Ast et al 2013). However, dual localization of peroxisomal proteins was predominantly reported to occur into the cytosol and into mitochondria (Ast et al 2013), merely one study in yeast described nuclear translocation of a peroxisomal NAD + -dependent glycerol 3-phosphate dehydrogenase (Jung et al 2010). The concurrent analysis of the intracellular distribution of catalase, another peroxisomal protein, demonstrated a comparable propiverine-mediated mislocalization from the peroxisomes to the cytosol and nucleus, thereby suggesting the presence of more generalized compound-mediated reduced or abrogated translocation to or import of peroxisomal proteins into peroxisomes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it is reported that peroxisomal proteins can be differentially localized within the cell depending on differential splicing, multiple targeting signals or phosphorylation (Fordor et al 2012;Ast et al 2013). However, dual localization of peroxisomal proteins was predominantly reported to occur into the cytosol and into mitochondria (Ast et al 2013), merely one study in yeast described nuclear translocation of a peroxisomal NAD + -dependent glycerol 3-phosphate dehydrogenase (Jung et al 2010). The concurrent analysis of the intracellular distribution of catalase, another peroxisomal protein, demonstrated a comparable propiverine-mediated mislocalization from the peroxisomes to the cytosol and nucleus, thereby suggesting the presence of more generalized compound-mediated reduced or abrogated translocation to or import of peroxisomal proteins into peroxisomes.…”
Section: Discussionmentioning
confidence: 99%
“…Post-translational modifications could also contribute to specificity of co-receptor binding of cargo proteins. To this end, it has been shown that phosphorylation of two serine residues close to the PTS2 signal of Gpd1p is important for efficient peroxisomal import (27).…”
Section: Discussionmentioning
confidence: 99%
“…4, left panel). Most of Pnc1p-GFP was found in cytosolic fractions (fractions [25][26][27]. However, a significant portion was present in fractions 2 and 3, co-fractionating with the peroxisomal matrix proteins Fox3p and Pcs60p.…”
Section: Gpd1p Forms a Heterodimeric Complex With Pnc1p-mentioning
confidence: 99%
See 2 more Smart Citations